Identification, physical mechanisms and impacts of drought–flood abrupt alternation: a review - Bai, Xiaoyan; Zhao, Chengxin; Tang, Yihan; Zhang, Zhenxing; Yang, Bing; Wang, Zhenxiong (Frontiers in Earth Science, 2023)
Abstract: Climate change has led to an increase in the frequency of extreme events, such as droughts and floods. This study aims to review the literature on the newly proposed phenomenon known as drought-flood abrupt alternation (DFAA). A comprehensive summary is provided to round up the numerous approaches employed to identify DFAA events, as well as its mechanisms and impacts. To provide a reference for responding and managing the emerging intensity and frequency of DFAA events, we conclude the paper by listing the insufficiency of current research and suggesting possible future research directions. As for the impact of DFAA, besides the loss of life and property which can be caused by any natural disaster, a DFAA event severely threatens food security by making a lasting and profound impact on the land productivity through the alteration of the combining conditions of water, soil, and temperature. As for the future research directions, existing indexes developed for DFAA identification should be improved by downscaling the temporal and spatial scale, with interactions of neighboring drought and flood events taken into consideration. What’s more, to better protect human society from the losses caused by DFAA, researches on accurate DFAA prediction are encouraged.